Effect of bacterial root symbiosis and urea as source of nitrogen on performance of soybean plants grown hydroponically for Bioregenerative Life Support Systems (BLSSs) - Paradiso, Roberta; Buonomo, Roberta; Dixon, Mike A.; Barbieri, Giancarlo; De Pascale, Stefania (Frontiers in Plant Science, 2015)
Soybean is traditionally grown in soil, where root symbiosis with Bradyrhizobium japonicum can supply nitrogen (N), by means of bacterial fixation of atmospheric N2. Nitrogen fertilizers inhibit N-fixing bacteria. However urea is profitably used in soybean cultivation in soil, where urease enzymes of telluric microbes catalyze the hydrolysis to ammonium, which has a lighter inhibitory effect compared to nitrate. Previous researches demonstrated that soybean can be grown hydroponically with recirculating complete nitrate-based nutrient solutions. In Space, urea derived from crew urine could be used as N source, with positive effects in resource procurement and waste recycling. However, whether the plants are able to use urea as the sole source of N and its effect on root symbiosis with B. japonicum is still unclear in hydroponics. We compared the effect of two N sources, nitrate and urea, on plant growth and physiology, and seed yield and quality of soybean grown in closed-loop Nutrient Film Technique (NFT) in growth chamber, with or without inoculation with B. japonicum. Urea limited plant growth and seed yield compared to nitrate by determining nutrient deficiency, due to its low utilization efficiency in the early developmental stages, and reduced nutrients uptake (K, Ca and Mg) throughout the whole growing cycle. Root inoculation with B. japonicum did not improve plant performance, regardless of the N source. Specifically, nodulation increased under fertigation with urea compared to nitrate, but this effect did not result in higher leaf N content and better biomass and seed production. Urea was not suitable as sole N source for soybean in closed-loop NFT. However the ability to use urea increased from young to adult plants, suggesting the possibility to apply it during reproductive phase or in combination with nitrate in earlier developmental stages. Root symbiosis did not contribute significantly to N nutrition and did not enhance the plant ability to use urea, possibly because of ineffective infection process and nodule functioning in hydroponics.